Behavioral and Occupational Health in Military Firefighters: An Understudied Population. Issue 3 (May 2022) - Moore, Brian A.; Judkins, Jason L.; Dyal, Mari-Amanda; Schlenk, Michael; Meyer, Eric; Straud, Casey L.; Mysliwiec, Vincent; Peterson, Alan L.; Baker, Monty T.
To our knowledge, no studies on health conditions in U.S. military firefighters exist. Data and demographics from the Defense Medical Epidemiology Database were analyzed on several shared medical issues among military personnel and civilian firefighters. Descriptive statistics and Chi-Square goodness of fit tests were conducted to support study aims. Between 2001 and 2015, substantial incidence rate increases (per 10, 000) of tinnitus, PTSD, insomnia, and OSA (2005–2015) were observed. Modest to large increases in depressive disorders, adjustment reaction, generalized anxiety disorder, and panic disorder were observed. Decreasing rates were observed for alcohol dependence, hypertension, and tobacco use disorder. While efforts have examined the impact of sustained operations on military members, first responder military subgroups like firefighters are deficient. Cognitive Behavior Therapy interventions are efficacious for preventing and reducing behavioral health problems; therefore, tailoring them specifically for U.S. military firefighters could significantly improve quality of life and long-term health.